A study on non-spherical cuttings transport in CBM well drilling by coupled CFD-DEM. Issue 1 (1st January 2019) - Shao, Bing; Yan, Yifei; Yan, Xiangzhen; Xu, Zhiqian
ABSTRACT: Due to the specificity of coal rock containing CBM (coal bed methane), large-sized cuttings from coal bed drilling present abnormal appearances which make the transport of cuttings more troublesome. Simulations of the transport of large-sized and non-spherical drilling cuttings in the horizontal well-bore annulus possesses both theoretical challenges and engineering worth. In this work, a coupled CFD-DEM model is developed and a multi-sphere method is adopted to construct the non-spherical cuttings particles including cubic and long flaky particles. Validation with the experimental data reveals the well applicability of the developed CFD-DEM model. The movements as well as the sedimentations of cuttings are discussed in detail. The influences of fluid velocity and particle shapes on the transport efficiency of cuttings are studied and more attention is paid to flaky cuttings. The results show that, with a consistent equivalent volume, relatively good performance happens to the 20 mm spherical particles while local piled bed appears to the flaky particles; however, cuttings in cubic particles behave the worst. In the chosen conditions, transport efficiency drops dramatically when the volume fraction of the flaky cuttings exceeds 10%. Work in this paper is expected to be able to be applied to CBM drilling engineering.